PENGARUH GAYA KEPEMIMPINAN, BUDAYA SEKOLAH DAN KOMITMEN KERJA TERHADAP EFEKTIVITAS SEKOLAH - Kristia Ningrum Natalia (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
This research was conducted at Madrasah Aliyah Miftahul Ulum Kec. Palengaan with a total sample of 53 people (sampling technique is random sampling). The purpose of this study are: 1) To describe and analyze how the description of the principal's leadership style, school culture and work commitment to school effectiveness in MA Miftahul Ulum Rek Kecamatan Palengaan Kabupaten Pamekasan. 2) To Test and analyze whether the principal's leadership style, school culture and work commitment simultaneously have a significant influence on the effectiveness of the School at MA Miftahul Ulum Rek Kecamatan Palengaan Kabupaten Pamekasan. 3) To Test and analyze whether leadership style, school culture and work commitment partially have a significant influence on School effectiveness in MA Miftahul Ulum Rek Kecamatan Palengaan Kabupaten Pamekasan. Analysis of data using SPSS, this type of research is explanatory research using quantitative research approaches. The results of the study show that: 1). Leadership is the ability to move, influence, motivate, invite, direct, advise, guide, instruct, govern, prohibit, and foster so that human intentions as media management will work in order to achieve administrative goals effectively and efficiently, that school culture is a belief, policies, norms, and habits in schools that can be formed, strengthened, and maintained through leaders and teachers in schools, work commitment is a person's orientation towards the organization in terms of loyalty, identification, and involvement. 2). Simultaneously, leadership, organizational culture and work commitment have a significant effect on school effectiveness Madrasah Aliyah Miftahul Ulum Rek Kerrek Kec. Palengaan Pamekasan Regency, evidenced by the calculated F value of 0.951 with a significance value of 0.04 which means less than 0.05. 3). Partially, leadership style, school culture and work commitment have a significant influence on school effectiveness, leadership style is evidenced by the value of t count is equal to 0.674 with a significance level of 0.04 (smaller than 0.05), then known work motivation with t value count of 0.303 with a significance level of 0.03 positive and significant effect on school effectiveness (smaller than 0.05) and Competence has a positive and significant effect with a value of t count of 1.146 with a significance level of 0.04 (smaller than 0.05).